2006
DOI: 10.1542/peds.2005-2564
|View full text |Cite
|
Sign up to set email alerts
|

The Infant Development, Environment, and Lifestyle Study: Effects of Prenatal Methamphetamine Exposure, Polydrug Exposure, and Poverty on Intrauterine Growth

Abstract: These findings suggest that prenatal methamphetamine use is associated with fetal growth restriction after adjusting for covariates. Continued follow-up will determine if these infants are at increased risk for growth abnormalities in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(168 citation statements)
references
References 38 publications
6
157
3
1
Order By: Relevance
“…MA is a powerful psychostimulant that upon administration blocks monoamine transporters for dopamine, serotonin, and norepinephrine and causes release of these neurotransmitters into the synaptic cleft, therefore resulting in a sustained presence of these neurotransmitters in the cleft (Kucaenski and Segal, 1994). While the literature on prenatal MA exposure is limited, there is an association between MA and low birth weight and length, decreased head circumference, and increased fetal distress (Chomchai et al, 2004;Little et al, 1988;Smith et al, 2006). Reductions in the volume of the caudate, putamen, globus pallidus, and hippocampus were observed in children who were prenatally exposed to MA (Chang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…MA is a powerful psychostimulant that upon administration blocks monoamine transporters for dopamine, serotonin, and norepinephrine and causes release of these neurotransmitters into the synaptic cleft, therefore resulting in a sustained presence of these neurotransmitters in the cleft (Kucaenski and Segal, 1994). While the literature on prenatal MA exposure is limited, there is an association between MA and low birth weight and length, decreased head circumference, and increased fetal distress (Chomchai et al, 2004;Little et al, 1988;Smith et al, 2006). Reductions in the volume of the caudate, putamen, globus pallidus, and hippocampus were observed in children who were prenatally exposed to MA (Chang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed recruitment methods for the IDEAL study have been reported previously. 4,27 This study was approved by the institutional review boards at each site, and written informed consent was obtained from all subjects. A National Institute on Drug Abuse Certificate of Confidentiality was obtained that assured confidentiality of information regarding the mothers' drug use.…”
Section: Methodsmentioning
confidence: 99%
“…1 Now at Curtin University of Technology, Perth, WA, Australia utero methamphetamine (MAMP) or amphetamine (AMP) exposure, either alone or in combination with other drugs such as cocaine. [3][4][5][6][7] Human neonatal outcomes after in utero exposure to methylenedioxy-derivatives of AMP, such as 3,4-methylenedioxymethamphetamine (MDMA) and 3,4-methylenedioxyamphetamine (MDA) are not well understood. Exposed infants may be identified by maternal self-report or chromatographic confirmation of MAMP, AMP, MDMA and/or metabolites in meconium.…”
Section: Introductionmentioning
confidence: 99%